Evaluation of Sidestream Darkfield Microscopy for Real-Time Imaging Acellular Dermal Matrix Revascularization - DeGeorge, Jr, Brent R; Olenczak, J Bryce; Cottler, Patrick S; Drake, David B; Lin, Kant Y; Morgan, Raymond F; Campbell, Christopher A (Annals of plastic surgery, 2016)
Acellular dermal matrices (ADMs) serve as a regenerative framework for host cell integration and collagen deposition to augment the soft tissue envelope in ADM-assisted breast reconstruction-a process dependent on vascular ingrowth. To date noninvasive intra-operative imaging techniques have been inadequate to evaluate the revascularization of ADM. We investigated the safety, feasibility, and efficacy of sidestream darkfield (SDF) microscopy to assess the status of ADM microvascular architecture in 8 patients at the time of tissue expander to permanent implant exchange during 2-stage ADM-assisted breast reconstruction. The SDF microscopy is a handheld device, which can be used intraoperatively for the real-time assessment of ADM blood flow, vessel density, vessel size, and branching pattern. The SDF microscopy was used to assess the microvascular architecture in the center and border zone of the ADM and to compare the native, non-ADM-associated capsule in each patient as a within-subject control. No incidences of periprosthetic infection, explantation, or adverse events were reported after SDF image acquisition. Native capsules demonstrate a complex, layered architecture with an average vessel area density of 14.9 mm/mm and total vessel length density of 12.3 mm/mm. In contrast to native periprosthetic capsules, ADM-associated capsules are not uniformly vascularized structures and demonstrate 2 zones of microvascular architecture. The ADM and native capsule border zone demonstrates palisading peripheral vascular arcades with continuous antegrade flow. The central zone of the ADM demonstrates punctate perforating vascular plexi with intermittent, sluggish flow, and intervening 2- to 3-cm watershed zones. Sidestream darkfield microscopy allows for real-time intraoperative assessment of ADM revascularization and serves as a potential methodology to compare revascularization parameters among commercially available ADMs. Thr SDF microscopy demonstrates that the periprosthetic capsule in ADM-assisted implant-based breast reconstruction is not a uniformly vascularized structure.